Towards a general prediction-model for the current-induced mobilisation of objects on the sea floor. (15th September 2018) - Menzel, Peter; Schütt, Clemens; Wranik, Henning; Paschen, Mathias; Drews, Anja
Abstract: The aim of this work was to quantify the physical conditions, required for the mobilisation of unexploded ordnance devices (UXO) on the sea floor. As a basis for this, the hydrodynamic processes around UXO were measured in the wind tunnel and the flume tank in terms of conditions, especially Reynolds numbers. From these experiments, the typical shape of a sandy sea floor in the close vicinity of an object, due to current-induced burial was determined. Knowing this, the model for current-induced mobilisation of objects was developed. The model assumes a critical dimensionless Moment Factor M F = a ⋅ R e b, where the parameters a and b had to be investigated. This was accomplished by performing a total number of 287 numerical simulations, wind-tunnel testings and flume tank experiments at different geometric scale factors (1:10, 1:5, 1:2 and 1:1). With the parameter values so determined, the model describes the critical situation of an arbitrary shaped cylinder-like object regarding the incident flow velocity, the immersed mass and the burial depth, as well as the length and the volume-averaged diameter of the object. Highlights: Unexploded ordnance devices (UXO) are a huge problem during offshore construction. Scour and burial of objects on the sea floor was described by using fluid mechanical methods. The mobilisation of UXO due to currents was examined for different Reynolds numbers. A prediction model for the mobilisation of UXO is presented. The prediction model can be applied for arbitrary objects on the sea floor.